Business ethics and ethical business - Audi, Robert, 1941- (Oxford University Press, 2009)
This work is a brief yet comprehensive introduction to the thought-provoking field of business ethics. It is organized into three parts that cover the role of business in society, the ethics of internal management, and the challenges of international business.